Cellulose-based straw and preparation method thereof

By using cellulose powder, cellulose nanofibers, cellulose nanocrystals and cellulose dissolving solution, the problems of non-degradability and poor water resistance of traditional straws are solved, and high strength, low water absorption and natural degradability are achieved. The effect of this meeting the needs of green and sustainable development.

CN119192688APending Publication Date: 2024-12-27SHANDONG SENXIN ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411393214.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional plastic straws are non-degradable and non-renewable. Substitute materials such as PLA, PBAT, starch, etc. on the market have problems such as high material costs, high mechanical brittleness, and poor water resistance, which are difficult to fully meet the needs of green and sustainable development.

Method used

Cellulose powder, cellulose nanofibers, cellulose nanocrystals and cellulose dissolving solution are used as the main raw materials, and a high-strength, low-water absorption, naturally degradable cellulose-based straw is formed through specific preparation methods, and a cellulose dissolving solution is used. As the adhesive, it is supplemented with a cellulose material network reinforcement.

Benefits of technology

It has achieved high-strength, low water absorption and naturally degradable straw products. Cellulose nanofibers and nanocrystals are supplemented with grading in the system, improving the density and strength of the product and meeting the needs of green and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192688A_ABST
    Figure CN119192688A_ABST
Patent Text Reader

Abstract

The invention relates to a cellulose-based straw and a preparation method thereof. The cellulose-based straw comprises the following raw materials in parts by mass: 10-50 parts of cellulose powder; 10 to 50 parts of cellulose nanofiber; 1 to 50 parts of cellulose nanocrystals; 10 to 60 parts of a cellulose dissolving solution; and 1-5 parts of a cross-linking agent. The cellulose dissolving solution is used as an adhesive, and the cellulose material with proper size and proportion is used as a network reinforcement, so that the straw with the cellulose as the main body material is obtained, and the straw has the characteristics of high strength, weak water absorption, natural degradation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a cellulose-based drinking straw and a method for preparing the same. Background Art

[0002] Straws are a common product in daily life. The most common ones are plastic straws, which are hollow products of specified sizes obtained by melting plastic masterbatches such as polypropylene at high temperature and then extruding them at a certain rate and cooling them through an extrusion die. However, traditional plastic straws have problems such as non-degradability, non-renewability, low recycling value, and white pollution. Straws made of polylactic acid (PLA), polybutylene adipate / terephthalate (PBAT), starch, paper, etc. have appeared on the market, but these straws also have their own advantages and disadvantages and cannot fully meet market demand and the concept of green and sustainable development. For example: The advantages of PLA straws are that they are degradable, safe, and can be injection molded for a good user experience. The disadvantages are high material cost, high mechanical brittleness, softening and deformation when encountering high-temperature liquids, uncontrollable natural degradation rate, and short shelf life of finished products. Paper straws are renewable and degradable, reducing white pollution, but most of the current paper straws are made of three layers co-rolled and bonded, with poor water resistance, easy to soften after soaking in water, and stratification, which gives consumers a poor user experience. Starch straws require food starch as raw material and cannot be used in high-temperature liquids. They will not become soft if used in cold water for a short period of time, but the surface will become sticky and the feel will be poor when used.

[0003] Cellulose is the most abundant natural polymer material in nature. Its renewable and biodegradable properties play an important role in sustainable development and environmental protection. Cellulose comes from a wide range of sources, such as trees, bamboo, cotton, wheat straw and sugarcane bagasse. Cellulose is widely used in the fields of household paper, specialty paper, textile products, cellulose ether, etc. However, cellulose has a large number of hydrogen bonds and high crystallinity within and between molecules, which makes cellulose difficult to dissolve and has no melting properties, thus greatly limiting the plasticity and secondary processing properties of cellulose materials.

[0004] Natural cellulose is insoluble in common organic solvents and dilute alkaline solutions, and requires special solvents and conditions to achieve dissolution. The solution formed by dissolving cellulose in a specific solvent is called cellulose solution. Cellulose solution has unique regeneration characteristics, and it only needs to be treated with specific chemical reagents or chemical processes to regenerate regenerated cellulose products. Currently, commercial regenerated cellulose products are limited to the regeneration preparation of pure cellulose solution, such as regenerated cellulose fiber (lyocell, viscose fiber), regenerated cellulose film (cellophane), etc. In addition, there are no related products related to cellulose solution derivatives. Summary of the invention

[0005] In order to solve the above problems, a cellulose-based straw is disclosed, comprising the following raw materials in parts by weight:

[0006] Cellulose powder: 10-50 parts;

[0007] Cellulose nanofibers: 10-50 parts;

[0008] Cellulose nanocrystals: 1-50 parts;

[0009] Cellulose dissolving solution: 10-60 parts;

[0010] Cross-linking agent: 1 to 5 parts. The present invention uses cellulose solution as an adhesive and cellulose material of appropriate size and proportion as a network reinforcement to obtain a straw with cellulose as the main material, which has the characteristics of high strength, weak water absorption, and natural degradation.

[0011] Preferably, the cellulose powder includes a first cellulose powder with a particle size greater than 150 mesh, a second cellulose powder with a particle size not greater than 150 mesh and greater than 100 mesh, and a third cellulose powder with a particle size not greater than 100 mesh and greater than 60 mesh, wherein the first cellulose powder accounts for 30-35wt%, the second cellulose powder accounts for 30-35wt%, and the rest is the third cellulose powder. The present application is not only about grading the cellulose powder, but in fact, the cellulose nanofibers and nanocrystals in the system also play a role in supplementing the grading of the cellulose powder, and their presence will make the system denser and the strength more in line with the requirements.

[0012] Preferably, the cellulose powder is bleached wood pulp powder, cotton pulp powder, or a combination of the two in any ratio;

[0013] The cellulose powder is prepared as follows: drying the raw material in a vacuum oven at 90-110° C. for 60-110 min;

[0014] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder.

[0015] Preferably, the cellulose dissolving solution is prepared as follows:

[0016] Then the pulp is placed in a specific solvent system, and the mass of the pulp put in accounts for 5-10wt% of the total mass of the specific solvent system.

[0017] Preferably, the specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6-8wt%, and the mass fraction of urea is 6-8wt%. The solvent system is precooled to -12°C to -7°C, the pulp is added in batches, and then stirred for 45-60 minutes to obtain a cellulose solution;

[0018] The pulp is cotton pulp or wood pulp.

[0019] Preferably, the cellulose nanocrystals are obtained in the following manner:

[0020] The pulp is placed in a sulfuric acid solution with a mass fraction of 40-70wt%, the mass of the pulp is 5-10% of the mass of the sulfuric acid solution, the reaction temperature is 50-105°C, the reaction is stirred for 2-3 hours, then neutralized and washed, homogenized at 500-900bar for 1-3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15-25%.

[0021] Preferably, the cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0022] Preferably, the cross-linking agent is polyvinyl alcohol, citric acid or starch.

[0023] On the other hand, the present application discloses a method for preparing a cellulose-based straw, comprising the following steps:

[0024] The cellulose solution, cellulose powder, cellulose nanofibers and cellulose nanocrystals are mixed and stirred evenly;

[0025] Then add the cross-linking agent and mix well;

[0026] Stir and age for 3 to 5 hours under vacuum at -5 to 5°C;

[0027] Under vacuum conditions, the temperature is naturally raised to 20-35°C, and then stirred and aged for 5-10 hours to obtain the original slurry after degassing;

[0028] In the aging process of the present application, the cellulose nanocrystals will still partially dissolve due to their short size, while the cellulose nanofibers are long fibers, which are more difficult to dissolve than the cellulose nanocrystals. After the aging is completed, the dissolved part, the undissolved part, and the part in between will form a cellulose system with a more uniform distribution from the molecular level to the micron level, and the density of the obtained product will be correspondingly improved.

[0029] When cellulose dissolves, the lower the temperature, the higher the dissolution rate and solubility. Therefore, in the first step of aging, by reasonably controlling the system temperature and time, the morphology of cellulose nanocrystals and cellulose nanofibers during the aging process can be regulated. Straw products require high strength and weak water absorption, so a process biased towards dissolution is required during the aging process to achieve product characteristics of high density, high strength, and weak water absorption.

[0030] At -5 to 5°C, cellulose nanocrystals tend to dissolve, and cellulose nanofibers also dissolve locally, dissociate long fibers, and roughen the fiber surface. The roughening of the surface of cellulose nanofibers also provides a stable anchor point for regeneration, further improving the strength of the regenerated sample.

[0031] The original slurry is formed and extruded by a twin-screw extruder or a single-screw extruder to obtain a straw;

[0032] Immerse the straw in the coagulation bath, soak it in clean water after the reaction is completed, rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; dry the cured composite material to obtain a dried composite material, and the drying temperature is 50-90°C;

[0033] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12-15 wt % and the mass fraction of sodium sulfate is 18-25 wt %.

[0034] Preferably, the wall thickness of the straw is 0.5-1.0 mm, the length of the straw is 150-300 mm, and the outer diameter of the straw is 4-10 mm.

[0035] When drying the straws, first place the straws to be dried in the drying fixture, and then put them into the drying box for drying;

[0036] The drying fixture comprises an upper drying plate and a lower drying plate, the upper drying plate is provided with a plurality of upper semicircular grooves for accommodating straws, the lower drying plate is provided with a lower semicircular groove matching the upper semicircular groove, and the upper semicircular groove and the lower semicircular groove are respectively provided with a plurality of vents;

[0037] The upper drying plate and the lower drying plate are respectively provided with a plurality of connection bolt holes for fastening connection, and the groove walls of the upper semicircular groove and the lower semicircular groove are provided with axial grooves extending along the axial direction to prevent the straw from being deformed during the drying process.

[0038] This application can bring the following beneficial effects:

[0039] 1. The present application uses cellulose solution as an adhesive and cellulose material of appropriate size and proportion as a network reinforcement to obtain a straw with cellulose as the main material, which has the characteristics of high strength, weak water absorption, and natural degradation.

[0040] 2. The present application is not only about grading cellulose powder, but in fact cellulose nanofibers and nanocrystals also play a role in supplementing the grading of cellulose powder in the system. Their presence will make the system denser and the strength more in line with the requirements.

[0041] 3. In the aging process of the present application, under suitable temperature and time conditions, cellulose nanocrystals tend to dissolve, and cellulose nanofibers also dissolve local microfibrils, dissociate long fibers, and roughen the fiber surface. A highly uniform and dense cellulose system is obtained, and the surface roughening of cellulose nanofibers also provides a stable anchor point for regeneration, further improving the strength of the regenerated sample. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0043] Figure 1 Schematic diagram of the structure of the drying fixture.

[0044] Figure 2 Schematic diagram of the explosion structure of the drying fixture. DETAILED DESCRIPTION

[0045] In order to clearly illustrate the technical features of this solution, this application is elaborated in detail below through specific implementation methods.

[0046] This application discloses a cellulose-based straw and a method for preparing the same. Since it is a material, it relies on its preparation method:

[0047] The steps include:

[0048] S1. Raw material preparation:

[0049] The cellulose powder is one or a combination of bleached wood pulp powder and cotton pulp powder in any ratio;

[0050] The cellulose powder is prepared as follows: drying the raw material in a vacuum oven at 90-110° C. for 60-110 min;

[0051] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder.

[0052] Therefore, the first cellulose powder has a particle size greater than 150 mesh, the second cellulose powder has a particle size not greater than 150 mesh and greater than 100 mesh, and the third cellulose powder has a particle size not greater than 100 mesh and greater than 60 mesh, wherein the first cellulose powder accounts for 30-35wt% and the second cellulose powder accounts for 30-35wt%, and the rest is the third cellulose powder.

[0053] The cellulose dissolving solution is prepared as follows:

[0054] Placing pulp in a specific solvent system, wherein the mass of the pulp input accounts for 5 to 10 wt% of the total mass of the specific solvent system;

[0055] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6-8wt%, and the mass fraction of urea is 6-8wt%. The solvent system is precooled to -12°C to -7°C, the pulp is added in batches, and then stirred for 45-60 minutes to obtain a cellulose solution;

[0056] The pulp is cotton pulp or wood pulp.

[0057] The cellulose nanocrystals are obtained in the following manner:

[0058] The pulp is placed in a sulfuric acid solution with a mass fraction of 40-70wt%, the mass of the pulp is 5-10% of the mass of the sulfuric acid solution, the reaction temperature is 50-105°C, the reaction is stirred for 2-3 hours, then neutralized and washed, homogenized at 500-900bar for 1-3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15-25%.

[0059] S2. Raw material mixing:

[0060] Mix 10 to 60 parts of cellulose solution, 10 to 50 parts of cellulose powder, 10 to 50 parts of cellulose nanofibers, and 1 to 50 parts of cellulose nanocrystals (i.e., cellulose nanocrystal slurry) and stir evenly;

[0061] Then add 1 to 5 parts of cross-linking agent and mix well;

[0062] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0063] The cross-linking agent is polyvinyl alcohol, citric acid or starch.

[0064] S3. Aging treatment:

[0065] Stir and age for 3 to 5 hours under vacuum at -5 to 5°C;

[0066] Under vacuum conditions, the temperature is naturally raised to 20-35°C, and then stirred and aged for 5-10 hours to obtain the original slurry after degassing;

[0067] S4. Extruding the original slurry using a twin-screw extruder or a single-screw extruder to obtain a straw.

[0068] The wall thickness of the straw is 0.5-1.0 mm, the length of the straw is 150-300 mm, and the outer diameter of the straw is 4-10 mm.

[0069] S5. Post-processing

[0070] Immerse the straw in the coagulation bath, soak it in clean water after the reaction is completed, rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; dry the cured composite material to obtain a dried composite material, and the drying temperature is 50-90°C;

[0071] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12-15wt% and the mass fraction of sodium sulfate is 18-25wt%;

[0072] When drying the straws, first place the straws to be dried in the drying fixture, and then put them into the drying box for drying;

[0073] like Figure 1-2 As shown, the drying fixture comprises an upper drying plate 1 and a lower drying plate 2, the upper drying plate 1 is provided with a plurality of upper semicircular grooves 3 for accommodating straws, the lower drying plate 2 is provided with a lower semicircular groove 4 matching the upper semicircular groove 3, and the upper semicircular groove 3 and the lower semicircular groove 4 are provided with a plurality of ventilation holes 7 respectively;

[0074] A plurality of connecting bolt holes 5 for fastening are respectively provided on the upper drying plate 1 and the lower drying plate 2 , and an axial groove 6 extending in the axial direction is provided on the groove walls of the upper semicircular groove 3 and the lower semicircular groove 4 .

[0075] When implementing it specifically, the following embodiments are performed:

[0076] Embodiment 1:

[0077] S101. Raw material preparation:

[0078] The cellulose powder is cotton pulp powder;

[0079] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 90° C. for 110 min;

[0080] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder.

[0081] Therefore, the first cellulose powder has a particle size greater than 150 mesh, the second cellulose powder has a particle size not greater than 150 mesh and greater than 100 mesh, and the third cellulose powder has a particle size not greater than 100 mesh and greater than 60 mesh, wherein the first cellulose powder accounts for 30wt%, the second cellulose powder accounts for 30wt%, and the rest is the third cellulose powder.

[0082] The cellulose dissolving solution is prepared as follows:

[0083] The pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass of the specific solvent system.

[0084] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0085] The cellulose nanocrystals are obtained in the following manner:

[0086] The pulp was placed in a 40wt% sulfuric acid solution, the mass of the pulp was 5% of the mass of the sulfuric acid solution, the reaction temperature was 50°C, the reaction was stirred for 3 hours, then neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15wt%.

[0087] S102. Raw material mixing:

[0088] Mix 10 parts of cellulose solution, 1 part of cellulose nanocrystals, 10 parts of cellulose powder, and 10 parts of cellulose nanofibers;

[0089] Add 1 part of cross-linking agent and mix well;

[0090] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0091] The cross-linking agent is polyvinyl alcohol.

[0092] S103. Aging treatment:

[0093] Stir and age for 5 hours under vacuum and -5°C. Then naturally heat to 20°C under vacuum, stir and age for 10 hours to obtain the original slurry after degassing;

[0094] S104. The original slurry is formed and extruded by a twin-screw extruder to obtain a straw.

[0095] The wall thickness of the straw is 0.5 mm, the length of the straw is 150 mm, and the outer diameter of the straw is 4 mm.

[0096] S105. Post-processing

[0097] The straw is immersed in the coagulation bath for 15 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material at a drying temperature of 50°C for 3 hours;

[0098] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12wt% and the mass fraction of sodium sulfate is 18wt%;

[0099] When drying the straws, first place the straws to be dried in the drying fixture, and then put them into the drying box for drying;

[0100] The drying fixture comprises an upper drying plate 1 and a lower drying plate 2, wherein the upper drying plate 1 is provided with a plurality of upper semicircular grooves 3 for accommodating straws, and the lower drying plate 2 is provided with a lower semicircular groove 4 matching the upper semicircular groove 3, and a plurality of vent holes 7 are respectively provided on the upper semicircular groove 3 and the lower semicircular groove 4;

[0101] A plurality of connecting bolt holes 5 for fastening are respectively provided on the upper drying plate 1 and the lower drying plate 2 , and an axial groove 6 extending in the axial direction is provided on the groove walls of the upper semicircular groove 3 and the lower semicircular groove 4 .

[0102] Five straws were placed in boiling water. Under the impact of boiling water, the time it took for the outer diameter of each straw to be significantly deformed was recorded. The average time was 127 minutes.

[0103] Five straws were completely immersed in room temperature water (21° C.), and the average change rate of the outer diameter after 3 hours was recorded to be 17.3%, and the average change rate of the outer diameter after 5 hours was recorded to be 17.3%.

[0104] Embodiment 2:

[0105] S201. Raw material preparation:

[0106] The cellulose powder is bleached wood pulp powder;

[0107] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 110° C. for 60 minutes;

[0108] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder.

[0109] Therefore, the first cellulose powder has a particle size greater than 150 mesh, the second cellulose powder has a particle size not greater than 150 mesh and greater than 100 mesh, and the third cellulose powder has a particle size not greater than 100 mesh and greater than 60 mesh, wherein the first cellulose powder accounts for 35wt%, the second cellulose powder accounts for 35wt%, and the rest is the third cellulose powder.

[0110] The cellulose dissolving solution is prepared as follows:

[0111] The pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 10wt% of the total mass of the specific solvent system.

[0112] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 8wt%, and the mass fraction of urea is 8wt%. The solvent system is precooled to -7°C, the pulp is added in batches, and then stirred for 60 minutes to obtain a cellulose solution;

[0113] The cellulose nanocrystals are obtained in the following manner:

[0114] The pulp was placed in a 70wt% sulfuric acid solution, the mass of the pulp was 10% of the mass of the sulfuric acid solution, the reaction temperature was 105°C, the reaction was stirred for 2h, then neutralized and washed, homogenized at 900bar for 3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 25wt%.

[0115] S202. Raw material mixing:

[0116] Mix 60 parts of cellulose solution, 50 parts of cellulose nanocrystals, 50 parts of cellulose powder, and 50 parts of cellulose nanofibers;

[0117] Add 5 parts of cross-linking agent and mix well;

[0118] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0119] The cross-linking agent is citric acid.

[0120] S203. Aging treatment:

[0121] Stir and age for 3 hours under vacuum and 5°C. Then naturally heat to 35°C under vacuum, stir and age for 5 hours to obtain the original slurry after degassing;

[0122] S204. The original slurry is formed and extruded using a twin-screw extruder to obtain a straw.

[0123] The wall thickness of the straw is 1.0 mm, the length of the straw is 300 mm, and the outer diameter of the straw is 10 mm.

[0124] S205. Post-processing

[0125] The straw is immersed in the coagulation bath for 15 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material at a temperature of 90°C for 3 hours;

[0126] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 15wt% and the mass fraction of sodium sulfate is 25wt%;

[0127] When drying the straws, first place the straws to be dried in the drying fixture, and then put them into the drying box for drying;

[0128] The drying fixture comprises an upper drying plate 1 and a lower drying plate 2, wherein the upper drying plate 1 is provided with a plurality of upper semicircular grooves 3 for accommodating straws, and the lower drying plate 2 is provided with a lower semicircular groove 4 matching the upper semicircular groove 3, and a plurality of vent holes 7 are respectively provided on the upper semicircular groove 3 and the lower semicircular groove 4;

[0129] A plurality of connecting bolt holes 5 for fastening are respectively provided on the upper drying plate 1 and the lower drying plate 2 , and an axial groove 6 extending in the axial direction is provided on the groove walls of the upper semicircular groove 3 and the lower semicircular groove 4 .

[0130] Five straws were placed in boiling water. Under the impact of boiling water, the time it took for the outer diameter of each straw to be significantly deformed was recorded. The average time was 142 minutes.

[0131] Five straws were completely immersed in room temperature water (21° C.), and the average change rate of the outer diameter after 3 hours was recorded to be 18.8%, and the average change rate of the outer diameter after 5 hours was recorded to be 18.8%.

[0132] Comparative Example 1:

[0133] S301. Raw material preparation:

[0134] The cellulose powder is cotton pulp powder;

[0135] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 90° C. for 110 min;

[0136] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder.

[0137] Therefore, the first cellulose powder has a particle size greater than 150 mesh, the second cellulose powder has a particle size not greater than 150 mesh and greater than 100 mesh, and the third cellulose powder has a particle size not greater than 100 mesh and greater than 60 mesh, wherein the first cellulose powder accounts for 30wt%, the second cellulose powder accounts for 30wt%, and the rest is the third cellulose powder.

[0138] The cellulose dissolving solution is prepared as follows:

[0139] The pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass of the specific solvent system.

[0140] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0141] S302. Raw material mixing:

[0142] 10 parts of cellulose solution, 1 part of cellulose nanocrystal solution (commercially available, 15 wt % concentration), 10 parts of cellulose powder, and 10 parts of cellulose nanofibers were mixed evenly;

[0143] Add 1 part of cross-linking agent and mix well;

[0144] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0145] The cross-linking agent is polyvinyl alcohol.

[0146] S303. Aging treatment:

[0147] Stir and age for 5 hours under vacuum and -5°C. Then naturally heat to 20°C under vacuum, stir and age for 10 hours to obtain the original slurry after degassing;

[0148] S304. The original slurry is formed and extruded by a twin-screw extruder to obtain a straw.

[0149] The wall thickness of the straw is 0.5 mm, the length of the straw is 150 mm, and the outer diameter of the straw is 4 mm.

[0150] S305. Post-processing

[0151] The straw is immersed in the coagulation bath for 15 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material at a drying temperature of 50°C for 3 hours;

[0152] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12wt% and the mass fraction of sodium sulfate is 18wt%;

[0153] When drying the straws, first place the straws to be dried in the drying fixture, and then put them into the drying box for drying;

[0154] The drying fixture comprises an upper drying plate 1 and a lower drying plate 2, wherein the upper drying plate 1 is provided with a plurality of upper semicircular grooves 3 for accommodating straws, and the lower drying plate 2 is provided with a lower semicircular groove 4 matching the upper semicircular groove 3, and a plurality of vent holes 7 are respectively provided on the upper semicircular groove 3 and the lower semicircular groove 4;

[0155] A plurality of connecting bolt holes 5 for fastening are respectively provided on the upper drying plate 1 and the lower drying plate 2 , and an axial groove 6 extending in the axial direction is provided on the groove walls of the upper semicircular groove 3 and the lower semicircular groove 4 .

[0156] Five straws were placed in boiling water. Under the impact of boiling water, the time it took for the outer diameter of each straw to be significantly deformed was recorded. The average time was 62 minutes.

[0157] Five straws were completely immersed in room temperature water (21° C.), and the average change rate of the outer diameter after 3 hours was recorded to be 22.4%, and the average change rate of the outer diameter after 5 hours was 23.2%.

[0158] Comparative Example 2:

[0159] S401. Raw material preparation:

[0160] The cellulose powder is cotton pulp powder;

[0161] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 90° C. for 110 min;

[0162] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder.

[0163] Therefore, the first cellulose powder has a particle size greater than 150 mesh, the second cellulose powder has a particle size not greater than 150 mesh and greater than 100 mesh, and the third cellulose powder has a particle size not greater than 100 mesh and greater than 60 mesh, wherein the first cellulose powder accounts for 30wt%, the second cellulose powder accounts for 30wt%, and the rest is the third cellulose powder.

[0164] S402. Raw material mixing:

[0165] 10 parts of cellulose solution (commercially available, 15 wt % concentration), 1 part of cellulose nanocrystal solution (commercially available, 15 wt % concentration), 10 parts of cellulose powder, and 10 parts of cellulose nanofibers were mixed evenly;

[0166] Add 1 part of cross-linking agent and mix well;

[0167] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0168] The cross-linking agent is polyvinyl alcohol.

[0169] S403. Aging treatment:

[0170] Stir and age for 5 hours under vacuum and -5°C. Then naturally heat to 20°C under vacuum, stir and age for 10 hours to obtain the original slurry after degassing;

[0171] S404. The original slurry is formed and extruded by a twin-screw extruder to obtain a straw.

[0172] The wall thickness of the straw is 0.5 mm, the length of the straw is 150 mm, and the outer diameter of the straw is 4 mm.

[0173] S405. Post-processing

[0174] The straw is immersed in the coagulation bath for 15 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material at a drying temperature of 50°C for 3 hours;

[0175] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12wt% and the mass fraction of sodium sulfate is 18wt%;

[0176] When drying the straws, first place the straws to be dried in the drying fixture, and then put them into the drying box for drying;

[0177] The drying fixture comprises an upper drying plate 1 and a lower drying plate 2, wherein the upper drying plate 1 is provided with a plurality of upper semicircular grooves 3 for accommodating straws, and the lower drying plate 2 is provided with a lower semicircular groove 4 matching the upper semicircular groove 3, and a plurality of vent holes 7 are respectively provided on the upper semicircular groove 3 and the lower semicircular groove 4;

[0178] A plurality of connecting bolt holes 5 for fastening are respectively provided on the upper drying plate 1 and the lower drying plate 2 , and an axial groove 6 extending in the axial direction is provided on the groove walls of the upper semicircular groove 3 and the lower semicircular groove 4 .

[0179] Five straws were placed in boiling water. Under the impact of boiling water, the time it took for the outer diameter of each straw to be significantly deformed was recorded. The average time was 52 minutes.

[0180] Five straws were completely immersed in room temperature water (21° C.), and the average change rate of the outer diameter after 3 hours was recorded to be 23.5%, and the average change rate of the outer diameter after 5 hours was 25.2%.

[0181] Comparative Example 3:

[0182] S501. Raw material preparation:

[0183] The cellulose powder is cotton pulp powder;

[0184] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 90° C. for 110 min;

[0185] The dried sample was then pulverized using a high-speed pulverizer and sieved through a 60-mesh sieve to obtain cellulose powder.

[0186] The cellulose dissolving solution is prepared as follows:

[0187] The pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass of the specific solvent system.

[0188] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0189] The cellulose nanocrystals are obtained in the following manner:

[0190] The pulp was placed in a 40wt% sulfuric acid solution, the mass of the pulp was 5% of the mass of the sulfuric acid solution, the reaction temperature was 50°C, the reaction was stirred for 3 hours, then neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15wt%.

[0191] S502. Raw material mixing:

[0192] Mix 10 parts of cellulose solution, 1 part of cellulose nanocrystals, 10 parts of cellulose powder, and 10 parts of cellulose nanofibers;

[0193] Add 1 part of cross-linking agent and mix well;

[0194] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0195] The cross-linking agent is polyvinyl alcohol.

[0196] S503. Aging treatment:

[0197] Stir and age for 5 hours under vacuum and -5°C. Then naturally heat to 20°C under vacuum, stir and age for 10 hours to obtain the original slurry after degassing;

[0198] S504. The original slurry is formed and extruded by a twin-screw extruder to obtain a straw.

[0199] The wall thickness of the straw is 0.5 mm, the length of the straw is 150 mm, and the outer diameter of the straw is 4 mm.

[0200] S505. Post-processing

[0201] The straw is immersed in the coagulation bath for 15 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material at a drying temperature of 50°C for 3 hours;

[0202] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12wt% and the mass fraction of sodium sulfate is 18wt%;

[0203] When drying the straws, first place the straws to be dried in the drying fixture, and then put them into the drying box for drying;

[0204] The drying fixture comprises an upper drying plate 1 and a lower drying plate 2, wherein the upper drying plate 1 is provided with a plurality of upper semicircular grooves 3 for accommodating straws, and the lower drying plate 2 is provided with a lower semicircular groove 4 matching the upper semicircular groove 3, and a plurality of vent holes 7 are respectively provided on the upper semicircular groove 3 and the lower semicircular groove 4;

[0205] A plurality of connecting bolt holes 5 for fastening are respectively provided on the upper drying plate 1 and the lower drying plate 2 , and an axial groove 6 extending in the axial direction is provided on the groove walls of the upper semicircular groove 3 and the lower semicircular groove 4 .

[0206] Five straws were placed in boiling water. Under the impact of boiling water, the time it took for the outer diameter of each straw to be significantly deformed was recorded. The average time was 103 minutes.

[0207] Five straws were completely immersed in room temperature water (21° C.), and the average change rate of the outer diameter after 3 hours was recorded to be 19.5%, and the average change rate of the outer diameter after 5 hours was 20.3%.

[0208] Comparative Example 4:

[0209] S601. Raw material preparation:

[0210] The cellulose powder is cotton pulp powder;

[0211] The cellulose powder is prepared as follows: the raw material is dried in a vacuum oven at 90° C. for 110 min;

[0212] The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder.

[0213] Therefore, the first cellulose powder has a particle size greater than 150 mesh, the second cellulose powder has a particle size not greater than 150 mesh and greater than 100 mesh, and the third cellulose powder has a particle size not greater than 100 mesh and greater than 60 mesh, wherein the first cellulose powder accounts for 30wt%, the second cellulose powder accounts for 30wt%, and the rest is the third cellulose powder.

[0214] The cellulose dissolving solution is prepared as follows:

[0215] The pulp is placed in a specific solvent system, and the mass of the pulp input accounts for 5wt% of the total mass of the specific solvent system.

[0216] The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6wt%, and the mass fraction of urea is 6wt%. The solvent system is precooled to -12°C, the pulp is added in batches, and then stirred for 45 minutes to obtain a cellulose solution;

[0217] The cellulose nanocrystals are obtained in the following manner:

[0218] The pulp was placed in a 40wt% sulfuric acid solution, the mass of the pulp was 5% of the mass of the sulfuric acid solution, the reaction temperature was 50°C, the reaction was stirred for 3 hours, then neutralized and washed, homogenized once at 500bar, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15wt%.

[0219] S602. Raw material mixing:

[0220] Mix 10 parts of cellulose solution, 1 part of cellulose nanocrystals, 10 parts of cellulose powder, and 10 parts of cellulose nanofibers;

[0221] Add 1 part of cross-linking agent and mix well;

[0222] The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

[0223] The cross-linking agent is polyvinyl alcohol.

[0224] S603. The original slurry is formed and extruded by a twin-screw extruder to obtain a straw.

[0225] The wall thickness of the straw is 0.5 mm, the length of the straw is 150 mm, and the outer diameter of the straw is 4 mm.

[0226] S604. Post-processing

[0227] The straw is immersed in the coagulation bath for 15 minutes. After the reaction is completed, it is soaked in clean water to rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; the cured composite material is dried to obtain a dried composite material at a drying temperature of 50°C for 3 hours;

[0228] The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12wt% and the mass fraction of sodium sulfate is 18wt%;

[0229] When drying the straws, first place the straws to be dried in the drying fixture, and then put them into the drying box for drying;

[0230] The drying fixture comprises an upper drying plate 1 and a lower drying plate 2, wherein the upper drying plate 1 is provided with a plurality of upper semicircular grooves 3 for accommodating straws, and the lower drying plate 2 is provided with a lower semicircular groove 4 matching the upper semicircular groove 3, and a plurality of vent holes 7 are respectively provided on the upper semicircular groove 3 and the lower semicircular groove 4;

[0231] A plurality of connecting bolt holes 5 for fastening are respectively provided on the upper drying plate 1 and the lower drying plate 2 , and an axial groove 6 extending in the axial direction is provided on the groove walls of the upper semicircular groove 3 and the lower semicircular groove 4 .

[0232] Five straws were placed in boiling water. Under the impact of boiling water, the time it took for the outer diameter of each straw to be significantly deformed was recorded. The average time was 73 minutes.

[0233] Five straws were completely immersed in room temperature water (21° C.), and the average change rate of the outer diameter after 3 hours was recorded to be 20.8%, and the average change rate of the outer diameter after 5 hours was 21.9%.

[0234] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.

Claims

1. A cellulose-based straw, characterized in that: Including the following raw materials by mass: Cellulose powder: 10-50 parts; Cellulose nanofibers: 10-50 parts; Cellulose nanocrystals: 1-50 parts; Cellulose dissolving solution: 10-60 parts; Cross-linking agent: 1 to 5 parts.

2. A cellulose-based drinking straw according to claim 1, characterized in that: The cellulose powder includes a first cellulose powder with a particle size greater than 150 meshes, a second cellulose powder with a particle size not greater than 150 meshes and greater than 100 meshes, and a third cellulose powder with a particle size not greater than 100 meshes and greater than 60 meshes, wherein the first cellulose powder accounts for 30-35wt% of the weight, the second cellulose powder accounts for 30-35wt% of the weight, and the rest is the third cellulose powder.

3. A cellulose-based drinking straw according to claim 2, characterized in that: The cellulose powder is one or a combination of bleached wood pulp powder and cotton pulp powder in any ratio; The cellulose powder is prepared as follows: drying the raw material in a vacuum oven at 90 to 110° C. for 60 to 110 minutes; The dried sample is then pulverized using a high-speed pulverizer, and then sieved using a vibrating screen to obtain a first cellulose powder, a second cellulose powder, and a third cellulose powder.

4. A cellulose-based drinking straw according to claim 2, characterized in that: The cellulose dissolving solution is prepared as follows: Then the pulp is placed in a specific solvent system, and the mass of the pulp put in accounts for 5-10wt% of the total mass of the specific solvent system.

5. A cellulose-based drinking straw according to claim 4, characterized in that: The specific solvent system is an alkali / urea / water system, wherein the mass fraction of NaOH is 6-8wt%, and the mass fraction of urea is 6-8wt%; the specific solvent system is precooled to -12°C to -7°C, the pulp is added in batches, and then stirred for 45-60 minutes to obtain a cellulose solution; The pulp is cotton pulp or wood pulp.

6. A cellulose-based drinking straw according to claim 5, characterized in that: The cellulose nanocrystals are obtained in the following manner: The pulp is placed in a sulfuric acid solution with a mass fraction of 40-70wt%, the mass of the pulp is 5-10% of the mass of the sulfuric acid solution, the reaction temperature is 50-105°C, the reaction is stirred for 2-3 hours, then neutralized and washed, homogenized at 500-900bar for 1-3 times, and concentrated to obtain a cellulose nanocrystal slurry with a solid content of 15-25%.

7. The sheet-like cellulose composite material according to claim 1, characterized in that: The cellulose nanofibers have a fiber length of 100 to 500 μm and a diameter of 10 to 50 nm.

8. A cellulose-based drinking straw according to claim 1, characterized in that: The cross-linking agent is polyvinyl alcohol, citric acid or starch.

9. A method for producing the cellulose-based drinking straw according to claim 6, characterized in that: The steps include: The cellulose solution, cellulose powder, cellulose nanofibers and cellulose nanocrystals are mixed and stirred evenly; Then add the cross-linking agent and mix well; Stir and age for 3 to 5 hours under vacuum at -5 to 5°C; Under vacuum conditions, the temperature is naturally raised to 20-35°C, and then stirred and aged for 5-10 hours to obtain the original slurry after degassing; The original slurry is formed and extruded by a twin-screw extruder or a single-screw extruder to obtain a straw; Immerse the straw in the coagulation bath, soak it in clean water after the reaction is completed, rinse off the residual sulfuric acid and salt to obtain a regenerated and cured composite material; dry the cured composite material to obtain a dried composite material, and the drying temperature is 50-90°C; The coagulation bath is an aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12-15 wt % and the mass fraction of sodium sulfate is 18-25 wt %.

10. A method for preparing a cellulose-based drinking straw according to claim 9, characterized in that: The wall thickness of the straw is 0.5-1.0 mm, the length of the straw is 150-300 mm, and the outer diameter of the straw is 4-10 mm; When drying the straws, first place the straws to be dried in the drying fixture, and then put them into the drying box for drying; The drying fixture comprises an upper drying plate and a lower drying plate, the upper drying plate is provided with a plurality of upper semicircular grooves for accommodating straws, the lower drying plate is provided with a lower semicircular groove matching the upper semicircular groove, and the upper semicircular groove and the lower semicircular groove are respectively provided with a plurality of vents; The upper drying plate and the lower drying plate are respectively provided with a plurality of connecting bolt holes for fastening connection, and the groove walls of the upper semicircular groove and the lower semicircular groove are provided with axial grooves extending in the axial direction.

Citation Information

Cited By

  • Cellulose tube and preparation method thereof

    CN120647979A